Small finds and ancient social practices in the North-West provinces of the Roman Empire - Whitmore, Alissa; Hoß, Stefanie 1980- (Oxbow Books, 2016)
"Small finds...the stuff of everyday life...offer archaeologists a fascinating glimpse into the material lives of the ancient Romans. These objects hold great promise for unravelling the ins and outs of daily life, especially for the social groups, activities, and regions for which few written sources exist. Focusing on amulets, brooches, socks, hobnails, figurines, needles, and other 'mundane' artefacts, these 12 papers use small finds to reconstruct social lives and practices in the Roman Northwest provinces. Taking social life broadly, the various contributions offer insights into the everyday use of objects to express social identities, Roman religious practices in the provinces, and life in military communities. By integrating small finds from the Northwest provinces with material, iconographic, and textual evidence from the whole Roman empire, contributors seek to demystify Roman magic and Mithraic religion, discover the latest trends in ancient fashion (socks with sandals!), explore Roman interactions with Neolithic monuments, and explain unusual finds in unexpected places. Throughout, the authors strive to maintain a critical awareness of archaeological contexts and site formation processes to offer interpretations of past peoples and behaviours that most likely reflect the lived reality of the Romans. While the range of topics in this volume gives it wide appeal, scholars working with small finds, religion, dress, and life in the Northwest provinces will find it especially of interest. Small Finds and Ancient Social Practices grew out of a session at the 2014 Theoretical Roman Archaeology Conference"...From publisher's website